First record of arthropods associated with Greigia juareziana (Bromeliaceae) - Fernando Hernández-Baz; Thorsten Krömer; Rosamond Coates (Revista Mexicana de Biodiversidad)
Here we present the first known records for Mexico and the Neotropics of arthropods associated with the terrestrial bromeliad Greigia juareziana. The site locality for the collection of the host species is the southeast portion of the San Martín Tuxtla volcano in the state of Veracruz, Mexico. Four species of arthropods were detected within the leaf axils and infloresences of the bromeliad, 3 of which were insects Anasa bellator, Proxis punctulatus and Apion sp. belonging to the Orders of Hemiptera and Coleoptera. The remaining species was identified only to family (Myriapoda: Chilopoda: Lithobidae).